Japanese Cave Site as a Historical Tourism Object in Aeramo Village, Aesesa District, Nagekeo Regency - Dhiki, Katarina; Du'e, Amalianus (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
This study aims to find out the history of the Japanese cave site in Aeramo village, also to find out its current condition and efforts to maintenance and utilize the Japanese cave site as a historical tourist attraction. The research method used is a qualitative method with a descriptive approach. The research was carried out at the Japanese cave site in Aeramo village, Aesesa district, Nagekeo Regency. Data was collected using direct observation techniques, unstructured interviews and documentation. Based on study results, it is known that the Japanese cave site in Aeramo village, which is located on Oki Sato hill and Oki Rane hill, was created during the Japanese occupation, which arrived in Mbay in 1942. Japanese cave sites are the result of forced labor (romusha) carried out by Japanese soldiers toward local communities. The current condition of Oki Sato Japanese cave seems poorly maintained like most abandoned buildings. While the Oki Rane Japanese cave is in fairly good condition. Maintenance efforts that have been carried out include building a wall to support the mouth of the cave, building a fence around the cave location, and planting trees (reforestation) around the hill.